Evaluation of the structural reduction in the design of a building with seismic isolators in the district of Tacna - Cuaquera Cardenas, Meylee Nayyomy (2021)
The investigation had as main objective to analyze the evaluation of the structural reduction in the design of a building with seismic isolators in the district of Tacna-2021, for this research the Faculty of Architecture and Urbanism of the Private University of Tacna was analyzed, for which it was carried out based on the Peruvian Technical Standards, relying on the Dynamic Isolation Catalog for the design of Insulators, then (03) Three Modelings were performed in the Etabs V19 Software, Structural Modeling without Seismic Isolators, Structural Modeling with Seismic Isolators and Modeling with Seismic Isolators-Structural Reduction. The Descriptive Method was used, systematically describing and analyzing the existing information regarding the results obtained by modifying the current conditions of the situation. As a result, a structural reduction of 20.47m2 of the columns was obtained, complying with the maximum displacements required by Standard E.031 "Seismic Isolation". Finally, it is concluded that although the reduction of the structural elements is not significant, the E.031 standard indicates that maximum drifts of 0.0035 in both directions should be considered, this clarification makes the structure more expensive since when placing the seismic isolators for each column becomes excessive, it is worth mentioning that the infrastructure in which we want to place the seismic isolators would have to be analyzed technically and economically to make an adequate decision on the matter, since with the results there is a minimal reduction in the geometry of the structural elements.